Effect of neuromuscular taping on musculoskeletal disorders secondary to the use of aromatase inhibitors in breast cancer survivors: a pragmatic randomised clinical trial. - Conejo Tirado, Inmaculada; Pajares, Bella; Alba-Conejo, Emilio; Cuesta-Vargas, Antonio (Springer Nature, 2018)
Background: Aromatase inhibitors reduce breast cancer recurrence rates in postmenopausal women by about 30% compared with tamoxifen while treatments differ. Unfortunately, nearly half of women taking AIs report AI-associated arthralgia (AIA), leading to therapy abandon in on third of patients, which could lead to cancer recurrence. The purpose of the current study was to evaluate the effectiveness of Neuromuscular Taping (NMT) in the treatment of AIA in women who have been treated of BC. Methods: This study included 40 BC survivors receiving endocrine therapy (either AIs or TMX) from Hospital Universitario Virgen de la Victoria (Málaga, Spain) suffered from AIA. Patients were randomized to one of the two groups that made this pilot study: A. Placebo intervention B. Real NMT. Clinical data were collected from medical history, grip strength, algometry measured, questionnaires and VAS scale. There have been three interventions prior to the completion of the study, 5 weeks later. The primary objective of this pilot study was to achieve an improvement of pain by 20% decrease of VAS. Results: Significant differences in measures of VAS (p = 0.009), global health status/QoL (p = 0.005), fatigue (p = 0.01) and pain (p = 0.04) were observed post intervention with NMT. Conclusions: An intervention by NMT to MSCM under treatment with AIs improves their subjective sensation of pain. In addition, this taping had an impact on variables related to the quality of life. This pilot study may be the basis for others to support the use of NMT for the treatment of AIAs, thereby improving their well-being and reducing the dropout rate.
Keywords: Mamas - Cáncer - Efectos de los medicamentos; Arthralgia; Breast cancer; Carpal tunnel syndrome; Estrogen deprivation; Hormonal therapy; Kinesio taping; Myalgia; Neuromuscular taping; Pressure pain threshold; Visual analogue scale; Aromatase inhibitors